2018
DOI: 10.3748/wjg.v24.i23.2413
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in non-invasive magnetic resonance imaging assessment of hepatocellular carcinoma

Abstract: Magnetic resonance (MR) imaging of the liver is an important tool for the detection and characterization of focal liver lesions and for assessment of diffuse liver disease, having several intrinsic characteristics, represented by high soft tissue contrast, avoidance of ionizing radiation or iodinated contrast media, and more recently, by application of several functional imaging techniques (i.e., diffusion-weighted sequences, hepatobiliary contrast agents, perfusion imaging, magnetic resonance (MR)-elastograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 96 publications
1
22
0
Order By: Relevance
“…The project was motivated by the fact that there is no phantom described in the literature as far as we know which simulates the typical pattern of HCC. Where the typical pattern of HCC appears in its hyper arterial enhancement and delayed washout, washout in the portal venous phase is typically with malignant lesions of size greater than 2 cm, and this is what the previous studies showed [ [37] , [38] , [39] ].…”
Section: Discussionsupporting
confidence: 59%
“…The project was motivated by the fact that there is no phantom described in the literature as far as we know which simulates the typical pattern of HCC. Where the typical pattern of HCC appears in its hyper arterial enhancement and delayed washout, washout in the portal venous phase is typically with malignant lesions of size greater than 2 cm, and this is what the previous studies showed [ [37] , [38] , [39] ].…”
Section: Discussionsupporting
confidence: 59%
“…The most common type of histology of primary liver cancer is HCC, which represents 90% of cases [ 22 , 23 ]. Difficulties in treatment and poor prognosis make it important to accurately detect HCC.…”
Section: Discussionmentioning
confidence: 99%
“…e quantitative and semiquantitative evaluation of the local tissue perfusion parameters is based on the changes in microcirculation and hemodynamics of the liver lesions [8,26,29]. GD-BOPTA provides information on the vascular changes and hepatocyte function, increasing the detection sensitivity of early HCC to 91-93% [30]. e relaxation rate of GD-BOPTA is significantly higher than that of the other types of gadolinium paramagnetic contrast agents; it is twice that of GD-DTPA, and even half dose can achieve the same strengthening effect [31].…”
Section: Discussionmentioning
confidence: 99%